2023
DOI: 10.1007/s11845-023-03385-8
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and procalcitonin during course of sepsis and septic shock

Abstract: Objective The study investigates the diagnostic and prognostic value of C-reactive protein (CRP) and procalcitonin (PCT) in patients with sepsis and septic shock. Background Limited data regarding the prognostic value of CRP and PCT during the course of sepsis or septic shock is available. Methods Consecutive patients with sepsis and septic shock from 2019 to 2021 were included monocentrically. Blood samples were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…C-reactive protein (CRP) is an inflammatory marker that has limited value in predicting 30-day ICU mortality. 41 The predictive indicators mentioned in previous studies largely overlap with those in our study. By employing LASSO regression, our study identified simple clinical and laboratory indicators for predicting ICU mortality in sepsis and achieved a higher prediction AUC, underscoring the significance of these ten indicators.…”
Section: Discussionsupporting
confidence: 79%
“…C-reactive protein (CRP) is an inflammatory marker that has limited value in predicting 30-day ICU mortality. 41 The predictive indicators mentioned in previous studies largely overlap with those in our study. By employing LASSO regression, our study identified simple clinical and laboratory indicators for predicting ICU mortality in sepsis and achieved a higher prediction AUC, underscoring the significance of these ten indicators.…”
Section: Discussionsupporting
confidence: 79%
“…Contrary to our results, the study of Schupp et al that investigates the diagnostic and prognostic value of C-reactive protein and procalcitonin in patients with sepsis and septic shock shows that CRP and procalcitonin have a poor predictive value about 30-day all-cause mortality. 29 Therefore, the present study highlights the need to further evaluate inflammatory biomarkers in patients with pulmonary septic shock and severe ARDS.…”
Section: Discussionmentioning
confidence: 90%
“…Sepsis is a common lethal condition that affects patients in the intensive care unit, and is associated with a high risk of mortality ( 1 , 2 ). The sepsis-induced inflammatory response leads to significant damage to the intestines and subsequent bacterial translocation, thereby causing the development of systemic infections and eventually resulting in death ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%